Adherence to Visits to Medical Institutions and Quality of Therapy after Acute Coronary Syndrome (according to the LIS Registry 3) - N. P. Zolotareva; A. V. Zagrebelny; M. L. Ginzburg; S. Yu. Martsevich; O. M. Drapkina (Столичная издательская компания, 2023)
Aim. The aim of the research is to evaluate the relationship between patients' adherence to visiting polyclinics after acute coronary syndrome (ACS) and the quality of the therapy they receive.Material and methods. The study was conducted on the basis of the LIS registers (LIS and LIS-3) (Lyubertsy study of mortality) in the Lyubertsy district of the Moscow region. To clarify the vital status of all patients discharged in the first 9 months of 2014 and 2018. from Lyubertsy district hospital 2, contact was established no earlier than 1 year after discharge, and in case of death, its cause was clarified. In the course of a telephone survey, information was obtained on the therapy taken, adherence to visits to medical institutions, a record of cases of cardiovascular events and invasive treatment, hospitalizations due to worsening of the course of the underlying disease for the period after discharge from the hospital was carried out. The search for patients who did not answer the phone call was carried out by studying the archives of polyclinics, using the Megaclinic statistical database, and the data of the individual rehabilitation program for the disabled. In the course of a telephone survey, the response was 60.5%, the search for the remaining patients through statistical databases, the archive of polyclinics made it possible to increase the total response to 87.2%.Results. In the LIS-3 registry, out of 104 patients discharged in 2014, the status was determined in 90 (86.5%) patients, out of 223 patients in 2018 - in 195 (87.4%) patients. During the survey, it was found that 172 patients are observed after discharge from the hospital, 53 patients are not observed at all in the medical facility after discharge. 11 (4.9%) people did not take any groups of medications at the time of the survey. In the group of patients who are highly committed to attending a health facility, the best quality of taking essential medications after discharge from the hospital was noted according to the survey: statins (88.2%, p<0.001), beta-blockers (86.4%, p<0.001) and antiplatelets (90.9%, p=0.001). In both groups, committed and not committed to attending a medical facility, there is a negative dynamics in the quality of taking medications after discharge from the hospital, however, in the group of patients committed to attending a medical facility, it was noted that the odds of taking antiplatelet agents after discharge was 3.4 times higher (OR 3.449, p=0.002), beta-blockers - 4 times (OR 4.103, p<0.001), statins - 4.5 times (OR 4.450, p<0.001), in relation to the group of patients who are not observed in the medical facility after discharge from the hospital.Conclusion. 1-6 years after discharge from the hospital after the reference event, the quality of therapy deteriorated significantly in both groups, mostly in non-adherent patients. Significant differences in the quality of medication intake (antiplatelet agents, statins, β-blockers) were noted in the group of adherents to visiting health care facilities in comparison with those who were not committed to visiting health facilities. It is obvious that high adherence to visits to healthcare facilities after discharge from the hospital is associated with better quality of medication intake. Despite improvements in the quality of adherence to clinical recommendations, the percentage of patients who independently refuse to take drug therapy (4.9%), regardless of visits to healthcare facilities after discharge from the hospital, remains.